2017
DOI: 10.1007/s00268-017-4056-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perspectives on Barriers to Surgical Care and the Impact of Mobile Surgery in Ecuador

Abstract: Mobile surgery provided by Cinterandes effectively overcomes many barriers patients encounter when seeking surgical care in rural Ecuador: decreased patient wait times, limited number of referrals to multiple locations, and decreased cost. Partnering with local clinics within the communities and bringing care much closer to patients' homes may provide a better patient friendly health care delivery system for rural Ecuador.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A 2017 study examining health referral systems among six Latin American countries found limited coordination and communication among all countries, with particularly severe problems in Mexico due to pervasive mistrust between providers [ 27 ]. Furthermore, a 2017 qualitative study in rural Ecuador similarly found that patient inconvenience, cost, and mistrust of hospitals were the three most cited barriers to surgical care [ 28 ]. As in our study, poor system-level coordination and a lack of patient-centric protocols exacerbate shortages in the referral system.…”
Section: Discussionmentioning
confidence: 99%
“…A 2017 study examining health referral systems among six Latin American countries found limited coordination and communication among all countries, with particularly severe problems in Mexico due to pervasive mistrust between providers [ 27 ]. Furthermore, a 2017 qualitative study in rural Ecuador similarly found that patient inconvenience, cost, and mistrust of hospitals were the three most cited barriers to surgical care [ 28 ]. As in our study, poor system-level coordination and a lack of patient-centric protocols exacerbate shortages in the referral system.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic laparoscopy under local anaesthesia and intravenous sedation has been reported for patients with an equivocal penetrating stab wound in the abdominal wall [ 18 ], and portability could make it feasible and easy to accomplish bedside diagnostic laparoscopy in the ward, emergency room, or intensive care unit. In addition, mobile medical services for remote and underdeveloped areas have drawn public attention and buses and trucks have been transformed into mobile operating rooms [ 19 , 20 ]. This new device may be an ideal alternative to standard equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these initiatives include the scale-up of prehospital emergency care via the creation of a 9-1-1 call system 3 , 4 and the provision of low-cost surgical care via mobile units to vulnerable populations in geographically remote areas through partnerships with not-for-profit organizations. 5 Timely, affordable, and safe access to emergency and essential surgical, obstetric, and anesthesia care is a priority for the Ecuadorian Government, currently tackling not only longstanding health system deficiencies but a backlog of urgent and elective surgical cases, stemming from resource allocation for the pandemic, as well. 6 …”
mentioning
confidence: 99%